Analysis of Risk Factors for Loculated Pleural Effusion in Patients with Tuberculous Pleural Effusion at dr. Zainoel Abidin Hospital - Purqan, Muhammad; Arliny, Yunita; Priyanto, Herry; Yanifitri, Dewi Behtri; Yanti, Budi (Jurnal Respirologi Indonesia, 2025)
Background: Loculated pleural effusion is an effusion that has a lenticular configuration with smooth borders and is relatively homogeneous and can cause atelectasis in the surrounding lung tissue and is a result of excessive inflammation. Tuberculous pleural effusion is characterized by chronic accumulation of fluid and inflammatory cells in the pleural cavity. If not treated appropriately, a loculated pleural effusion can be life-threatening. This study aims to assess risk factors for loculated pleural effusion in TB pleural effusion patients. Method: This is an observational, analytical research with a cross-sectional design. The research sample was taken based on a consecutive sampling technique from TB pleural effusion patients treated at dr. Zainoel Abidin Hospital, Banda Aceh, from January 2024 to April 2024. Results: This study shows a relationship between age, kidney failure and diabetes mellitus on the incidence of loculated pleural effusion in TB pleural effusion patients (P<0.05). Age ≥46 years old has a 12.57 times risk, kidney failure 5.50 times and DM 14.5 times against the incidence of loculated pleural effusion. Gender, anemia, human immunodeficiency virus (HIV), pleural fluid analysis results and positive culture did not correlate with loculated pleural effusion (P>0.05). Conclusion: Age, kidney failure and diabetes mellitus are risk factors for loculated pleural effusion. The increase in age-related risk is associated with chronic inflammation, called inflammaging. Increasing age is also associated with changes in the composition and function of lung cells, making the clearance of pathogens difficult. Intense inflammation and difficulty in clearing pathogens also contribute to the association of kidney failure and diabetes mellitus with loculated pleural effusion.